1999
DOI: 10.3141/1666-12
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Real-Time Bus Arrival Time Prediction with GPS Data

Abstract: Bus headway in a rural area is usually much larger than that in an urban area. Providing real-time bus arrival information could make the public transit system more user-friendly and thus enhance its competitiveness among various transportation modes. As part of an operational test for rural traveler information systems currently ongoing in Blacksburg, Virginia, an experimental study has been conducted on forecasting the arrival time of the next bus with AVL techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(53 citation statements)
references
References 0 publications
0
53
0
Order By: Relevance
“…Broach et al, 2012) and bus travel (e.g. Lin and Zeng, 1999;Mazloumi et al, 2010), we are not aware of any 5 The predominance of SP data is generally true for the literature on the valuation of travel attributes. Among those studies that are (at least partially) based on RP data are Lam and Small (2001), Brownstone and Small (2005) and Börjesson (2008).…”
Section: Introductionmentioning
confidence: 99%
“…Broach et al, 2012) and bus travel (e.g. Lin and Zeng, 1999;Mazloumi et al, 2010), we are not aware of any 5 The predominance of SP data is generally true for the literature on the valuation of travel attributes. Among those studies that are (at least partially) based on RP data are Lam and Small (2001), Brownstone and Small (2005) and Börjesson (2008).…”
Section: Introductionmentioning
confidence: 99%
“…Lin et al [7] suggested an arrangement of transport arrival time forecast calculations for a travel information system framework executed in Blacksburg, Virginia. Four calculations were presented with various assumptions on input information and were perform better than a few calculations from the literature.…”
Section: Related Workmentioning
confidence: 99%
“…As implied earlier, most of the models found in the literature (e.g., Kalaputapu and Demetsky 1995;Lin and Zeng 1999;Wall and Dailey 1999;Farhan et al 2002) have included bus dwell times along any link in the travel time of that link (i.e., link travel time includes running plus dwell times). As such, these models cannot consider explicitly the effect of late or early bus arrivals at bus stops on the dwell times at those stops and vice versa.…”
Section: Approachmentioning
confidence: 99%
“…Several researchers (Kalaputapu and Demetsky 1995;Lin and Zeng 1999;Wall and Dailey 1999) have used AVL (and less often APC) data to develop models specifically for bus travel time prediction. The motivation for developing these models was mostly for providing information to transit riders on expected bus arrival times with virtually no sensitivity of such models to operations control strategies.…”
Section: Introductionmentioning
confidence: 99%